40 years of excellence: An overview of Technovation and a roadmap for future research. (August 2021) - Dabić, Marina; Marzi, Giacomo; Vlačić, Božidar; Daim, Tugrul U.; Vanhaverbeke, Wim
Abstract: The International Journal of Technological Innovation, Entrepreneurship and Technology Management ( Technovation ) is a flagship journal in the fields of management and technological innovation. This renowned position is largely a result of academic interest, as demonstrated by the large number of citations received from other prestigious journals, as well as downloads from across the globe. This study honors the 40th anniversary of Technovation and provides an overview of the journal's accomplishments since its conception in 1981 using Thomson Reuters Web of Science Core Collection database, complemented by both the Elsevier Scopus and EBSCO Business Premier databases, as well as the journal's webpage. This study highlights the main contributors (i.e. authors, universities, countries accountable for the journal's high ranking), the most cited articles, and the thematic profile of the journal through an extensive bibliometric analysis of Technovation publications. Finally, this study outlines growing research trends and proposes trajectories for future research. Highlights: The International Journal of Technological Innovation, Entrepreneurship and Technology Management ( Technovation ) commemorates the 40th anniversary in 2020. A bibliometric overview and content analysis of the journal since its conception in 1981. Identification of main contributors (i.e. authors, universities, countries accountable for the journal's high ranking), the most cited articles, and the thematic profile of the journal. This overview highlights  Technovation  predominant research themes and proposes trajectories for future research.